Distribution of α amylase along the alimentary tract of two Mediterranean fish species, the parrotfish Sparisoma cretense L. and the stargazer, Uranoscopus scaber L - PAPOUTSOGLOU, E.S.; LYNDON, A.R. (Mediterranean Marine Science, 2003)
There is very little information available for the only Mediterranean species of parrotfish ( Sparisoma cretense) and its feeding habits, especially since most other parrotfish species are associated with coral reefs. The same lack of information is true for another fish species, the stargazer ( Uranoscopus scaber), which is carnivorous, and important for local fisheries in the Mediterranean. Comparative information is presented concerning the digestive activity and capacity for alpha amylase for these species with completely different feeding strategies, as well as main location(s) of carbohydrate digestion along their digestive tract. Alphaamylase activity and capacity is significantly higher in S. cretensethan U. scaber(p<0.05). Activity in S. cretense is very high, comparable to levels reported for carp and tilapia. It is similar in anterior and posterior intestine, however, the posterior intestine comprises a more important role in alpha amylase capacity. In U. scaber, activity is present in pyloric caeca and intestine. Levels are very low, comparable to levels reported for other benthic marine carnivores. There is no difference between activities in intestine and pyloric caeca. However, activity is higher in the anterior part of the intestine, lower in the posterior intestine and absent in the stomach. Such information is thought to be beneficial for improving knowledge on the biology of the examined species, and the physiology of nutrition, as well as for assisting towards understanding these processes in other, more valuable species for aquaculture. Also, the possibility of using the stargazer alimentary tract, especially its pyloric caeca as a model system is discussed.